2020
DOI: 10.3390/su12219220
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics—How and What Do University Students Know about the Emerging Environmental Sustainability Issue?

Abstract: For a successful transition towards sustainability, people need information and knowledge to understand the complex interconnectedness of social, natural, and social-natural systems. In order for people to be able to take a position on a number of environmental and social issues, and make decisions arising from these challenges, they need to use environmental literacy. We have come up with a tool to answer the question of how students access information about new environmental topics in the media, and how they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…In the presurvey, students defined microplastics as small plastic particles. The knowledge gaps regarding the sources and environmental and health impacts we found were the same as reported in the literature. In the feedback form, the identification of microplastics using this protocol received positive feedback from the students (see Figure ).…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…In the presurvey, students defined microplastics as small plastic particles. The knowledge gaps regarding the sources and environmental and health impacts we found were the same as reported in the literature. In the feedback form, the identification of microplastics using this protocol received positive feedback from the students (see Figure ).…”
Section: Resultsmentioning
confidence: 73%
“…A successful transition to sustainability requires an informed society . It is well-known that microplastics are small plastic particles, but there are still knowledge gaps regarding their sources, occurrence, and impacts. We aimed to address this gap with input designed on this topic. There is also a difference in how media communicate the risks induced by microplastics and how science communicates those facts .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, universities, institutions, and companies are aiming to reduce the use of single-use plastics due to the fact that plastic litter and plastic degradation cause negative impacts on the environment. Recent publications releasing research conducted on university students on the issue of microplastics revealed that most students from the Czech Republic have a partial knowledge of the topic (Janoušková et al, 2020), while students in Germany associated microplastics with negative consequences (Raab & Bogner, 2021). However, a Chinese study on public awareness in Shanghai revealed that the majority of the respondents were unfamiliar with microplastic pollution (Deng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%